2019
DOI: 10.1002/adhm.201900036
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Treatment with Stimuli‐Responsive Nanoagents: Recent Advances and Future Perspectives

Abstract: Atherosclerosis is the root of approximately one‐third of global mortalities. Nanotechnology exhibits splendid prospects to combat atherosclerosis at the molecular level by engineering smart nanoagents with versatile functionalizations. Significant advances in nanoengineering enable nanoagents to autonomously navigate in the bloodstream, escape from biological barriers, and assemble with their nanocohort at the targeted lesion. The assembly of nanoagents with endogenous and exogenous stimuli breaks down their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 246 publications
(289 reference statements)
0
46
0
Order By: Relevance
“…In advanced atherosclerotic lesions, intracellular and extracellular ROS levels increased, [ 6 ] thus opening big opportunities to develop intelligent drug delivery systems that are responsive toward a biologically relevant environment of inflamed blood vessels for enhancing drug delivery. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…In advanced atherosclerotic lesions, intracellular and extracellular ROS levels increased, [ 6 ] thus opening big opportunities to develop intelligent drug delivery systems that are responsive toward a biologically relevant environment of inflamed blood vessels for enhancing drug delivery. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Moreover, PC SV showed a relatively constant hydrodynamic diameter after long-term storage at room temperature, indicating its favorable stability properties (Fig.S3). This good stability of nano-carrier in physiological condition was important and bene cial for their in vivo application and intravenous injection [17][18][19] . In addition, surface zeta potential analysis showed that BPC had a zeta potential of − 20.8 ± 0.8 mV, whereas PC S (− 25.4 ± 1.5 mV) and PC SV (− 38.8 ± 1.7 mV) have lower values ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, stenting and nanoparticle (NP) technology are used to treat atherosclerosis [ 7 ]. However, both the drug-eluting stent and the bare metal stent cause restenosis and stent thrombosis to a certain extent [ 8 ]. Much of the NP technology that might be used for drug delivery utilize organic, inorganic or metallic materials that show cytotoxicity and low biocompatibility-features that need to be overcome in order for this technology to be used in the treatment of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%